KEPEMIMPINAN IDEAL PADA ERA GENERASI MILENIAL - Danang Nugroho; Sheila Mita Agustin; Wanti Nurhayanti; Nuriddini Sri Rizki; Yusup Ismail; Vina Sri Wulan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Leadership is an important aspect of management and is necessary in any organization. Managers organize and manage available resources, but also influence and direct others to achieve the best results. The success of management depends on the management style used and the satisfaction of subordinates.Being a good leader for the current and future generations is a big challenge. As time goes by, many leaders emerge depending on the demands of the environment. Effective management in the millennial generation era will be possible by qualifying leaders as reliable, intellectual, and intellectually talented leaders with a long-term vision. However, a good leader must also have honesty, integrity and honesty for the benefit of the people.Millennial leadership must support the independence and entrepreneurial spirit of the millennial generation. Strengthening the nation requires a spirit of independence and entrepreneurship which is the most important foundation. Millennial leaders must encourage and support the spirit of innovation, creativity and courage in creating new opportunities and overcoming challenges with an independent and entrepreneurial approach.